Analisa Biaya Makan pada Panti Asuhan Putra Utama 1 Jakarta Timur - Manalu, Waisaktini Margareth; Simamora, Sesen Claudya (Universitas Muhadi Setiabudi, 2024)
The nutrition problem in elementary school children is influenced by the daily food intake they consume. A child's nutritional status affects their level of health and the harmony between physical and mental development during their growth. The prevalence of malnutrition in Indonesian children aged 6-12 years is classified as underweight at 6.8% and severely underweight at 2.4%. Nutritional issues occur, partly due to low intake of nutrients such as energy intake in both the past and present. Malnutrition or poor nutritional status can occur due to inadequate energy intake. The prevalence of inadequate energy intake in children aged 6-12 years in DKI Jakarta is 41.8%. This study was conducted to analyze the cost of meals and the relationship between energy intake and nutritional status in children at Panti Asuhan Putra Utama 1 East Jakarta. The study used a cross-sectional design. Data analysis used Univariate and Bivariate with a chi-square test. The results of this study showed that the cost of meals per day for cycles 5 and 7 was IDR 20,508 thousand and IDR 21,201 thousand, respectively. Normal nutritional status was 71.7%, and abnormal nutritional status was 28.3%. There was no relationship between energy intake and nutritional status (p-value = 0.708). The conclusion of this study is that there is no relationship between energy intake and nutritional status, as well as a lack of availability of meal options in daily feeding.